1998
DOI: 10.1007/s000180050128
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of plant transgenes as a consequence of diverse cellular defence responses

Abstract: Linked and unlinked copies of transgenes and related endogenous genes in plants can be epigenetically silenced by homology-based mechanisms that operate at either the transcriptional or post-transcriptional level. Transcriptional inactivation is associated with promoter homology and meiotically heritable methylation. Post-transcriptional silencing requires homology in protein-coding regions and is fully reversed during meiosis. Recently, the notion that both of these processes reflect the action of different h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 70 publications
(76 reference statements)
0
38
1
Order By: Relevance
“…McClintock (1984) invoked the concept of genomic shock, which she defined as a preprogrammed response to an unusual challenge that led to extensive restructuring of the genome. A possible contributor to the "unusual challenge" is epigenetic gene silencing, which is triggered by homologous gene-gene interactions (Meyer and Saedler, 1996;Matzke and Matzke, 1998). The sudden union of redundant and diverged homeologous sets of genes in allopolyploids could trigger widespread gene silencing (Leitch and Bennett, 1997;Henikoff and Comai, 1998b;Rieseberg and Noyes, 1998) with accompanying changes in chromatin structure and DNA methylation (Henikoff and Matzke, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…McClintock (1984) invoked the concept of genomic shock, which she defined as a preprogrammed response to an unusual challenge that led to extensive restructuring of the genome. A possible contributor to the "unusual challenge" is epigenetic gene silencing, which is triggered by homologous gene-gene interactions (Meyer and Saedler, 1996;Matzke and Matzke, 1998). The sudden union of redundant and diverged homeologous sets of genes in allopolyploids could trigger widespread gene silencing (Leitch and Bennett, 1997;Henikoff and Comai, 1998b;Rieseberg and Noyes, 1998) with accompanying changes in chromatin structure and DNA methylation (Henikoff and Matzke, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Another is "genome shock," in which hybridization elicits restructuring of the genome, such as through changes to chromosomal organization or mobilization of repetitive sequences (McClintock, 1984). More recent studies indicate that genome shock could be associated with epigenetic effects such as the gene silencing triggered by homologous gene-gene interactions (Meyer and Saedler, 1996;Matzke and Matzke, 1998). In support of this hypothesis, it has been found that in allopolyploids the hybridization event is accompanied by changes in gene expression patterns, chromatin structure, and DNA methylation as well as sequence elimination (Henikoff and Matzke, 1997;Leitch and Bennett, 1997;Henikoff and Comai, 1998;Rieseberg and Noyes, 1998;Comai et al, 2000;Pikaard, 2001;Rieseberg, 2001;Madlung et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in a wide variety of organisms have shown that the structure and function of a segment of DNA can be profoundly affected by the presence of homologous sequences (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The impact of homologous sequences can be dramatic, ranging from changes in DNA sequence and methylation to changes in chromatin structure and global chromatin architecture.…”
mentioning
confidence: 99%